Gendered citizens in the new Indonesian democracy - Sen, Krishna (Association for the Publication of Indonesian and Malaysian Studies Inc., 2002)
This article was written prior to Megawati's rise to the presidency. It was primarily a polemical response to the widespread reporting in Indonesian media of the Islamic rejection of the prospect of a woman president. The polemical ground has shifted, but the questions raised are abiding ones: does the establishment of electoral democracy change the gendered relations of power in Indonesia? Will democracy give women a greater political say than they had under Suharto's military dominated authoritarian regime?